Transcriptomics and metabolomics reveal tolerance new mechanism of rice roots to Al stress - Wang, Jingbo; Su, Chang; Cui, Zhibo; Huang, Lixiang; Gu, Shuang; Jiang, Sixu; Feng, Jing; Xu, Hai; Zhang, Wenzhong; Jiang, Linlin; Zhao, Minghui (Frontiers in Genetics, 2023)
The prevalence of soluble aluminum (Al) ions is one of the major limitations to crop production worldwide on acid soils. Therefore, understanding the Al tolerance mechanism of rice and applying Al tolerance functional genes in sensitive plants can significantly improve Al stress resistance. Recent molecular genetic studies have identified a number of genes involved in Al resistance in rice, although the exact underlying Al resistance mechanism is still unclear. In this study, transcriptomics and metabolomics analyses were performed to reveal the mechanism of Al tolerance differences between two rice landraces with different Al tolerance. A total of 935 and 1126 differentially expressed genes (DEGs) were identified in Al-tolerant genotype Shibanzhan (KR) and Al-sensitive genotype Hekedanuo (MR) between the control group and Al stress group, respectively. KEGG enrichment analyses showed a close relationship between DEGs and differential metabolites (DMs). A total of 88 DMs in KR and 27 DMs in MR were significantly different between the 100µM AlCl3 treatment group and the control group. Transcriptomics and metabolomics analysis showed that DEG related to phenylpropanoid biosynthesis was highly enriched in KR and MR after Al stress, indicating that phenylpropanoid biosynthesis may be closely related to Al tolerance. E1.11.1.7 (peroxidase) was the most significant enzyme of phenylpropanoid biosynthesis in KR and MR under Al stress and is regulated by multiple genes. Among them, Os06g0521900 (which encodes a lignin-forming anionic peroxidase) showed various degrees of difference in two landraces, and the difference in KR was more significant. The contents of coniferyl alcohol and its aldehyde (which are precursors of the lignin polymer) were decreased in MR under Al stress. These may be the main reasons for the difference in Al tolerance between two landraces. We further identified that two candidate genes Os02g0770800 and Os06g0521900 may be involved in the regulation of Al tolerance in rice. Our results not only reveal the resistance mechanism of rice to Al stress to some extent, but also provide a useful reference for the molecular mechanism of different effects of Al poisoning on plants.